SAT0622-HPR SAFETY IN PATIENTS WITH RHEUMATOID ARTHRITIS IN BIOLOGICAL TREATMENT OVER 65 YEARS OF AGE. (2nd June 2020) - Crespo Golmar, A.; Moriano, C.; González Fernández, I.; Larco Rojas, X. E.; López Robles, A.; Pérez Sandoval, T.
Abstract : Background: A bias has been described with the lowest prescription of biologic treatments (bDMARD) in patients with rheumatoid arthritis (RA) in the elderly, despite presenting activity rates comparable to young population and higher risk of functional disability. This could be due to concerns about co-morbidities and polypharmacy1. Objectives: 1) To define the characteristics of patients with RA ≥65 years and bDMARD to follow up in the Day Hospital of University Assistance Complex of León during the last year. 2) To record the incidence rate (IT) and ratio of incidence rates (RDI) of infections, neoplasms and cardiovascular events (CD) during the course of your therapy. Methods: Observational, retrospective study of patients diagnosed with RA according to ACR 1987 and/or ACR 2010 criteria in intravenous biological treatment during 2019 with ≥65. Results: 40 patients with an average age at diagnosis of 55.9±15.76 years were included, 67.5 % of them were women. The average duration of the disease was 17.65±13.15 years. 40% had a history of smoking, 35% hypertension, 20% dyslipemia and 20% diabetes mellitus. A 97.5% were positive FRRA, 57% positive ACPA, 37.5% nodular and 65% erosive. As for pre-treatment, 70% had been with conventional (cDMARD) ≥2DMARD (Methotrexate (MTX) (92.5%) and Leflunomide (60%)). The mean dose of prednisone was 8.79 ±10.14 mg/day. The incidence rate of infections was 1.5%, and neoplasms and CD were 0.75% per person-years. The age at the beginning of the first bDMARD was 67.45 ± 8 years, the second (n=20) 67.98±6.64 and the third (n=7) 71.79±7.49. The first biological was a 52.5% anti-TNF, 5% anti-CTLA4, 30% anti-CD20 and 12.5% antiIL6 (25% monotherapy and combined with MTX 57.5%). The second was 30% anti-TNF, 25% antiCTLA4, 15% antiIL6 and 30% antiCD20 (50% in monotherapy and 40% methotrexate); with the third anti-TNF 42.85%, antiCTLA4 14.29%, antiIL6 14.29% and antiCD20 28.57% (42.86% in monotherapy and 42.46 with methotrexate). The mean doses of prednisone were 6.08±6.82, 4.38±7.21 and 6.95±5.94 mg/day respectively. The IT of bDMARD infections were 8.81%, 19.81% and 7.4% person-years; of neoplasia 1.04%, 0 and 0; and EC 3.63%, 0 and 1.85 person-years. The RTIs with first, second and third biological infections were: 5.88, 13.25, 4.95; with neoplasms 1.38; with EC 1.38, 0 and 0.69. The mean total accumulated corticosteroid dose was 17.69±15.01 mg/day. Conclusion: 1) Patients over 65 years old receiving bDMARD in our Day Hospital in 2019 were long-standing RA with aggression data, who had not responded to ≥2 cDMARD and required medium-high doses of prednisone. 2) In our sample there is a link between incidence of infection and the introduction of biological therapy, which is maintained with the increasing age of our patients, and it is not so clear with neoplasms and CD. These data are consistent with the existing literature 1, 2, 3 . 3) Larger, comparative studies with RA under 65 years are needed, but it is reasonable to conclude that if bDMARD is required, elderly patients could be a high-risk group for infections, requiring special monitoring and follow-up. References: [1]Alla Ishchenko, Rik J. Lories. Safety and Efficacy of Biological Disease-Modifying Antirheumatic Drugs in Olfer Rheumatoid Arthritis Patients: Staying the distance. Drugs Aging 2016;(33):387-398. [2]Atsuko Murota, Yuko Kaneko, Kunihiro Yamaoka y Tsutomu Takeuchi. Safety of Biologic Agents in Elderly Patients with Rheumatoid Arthritis. J Rheumatol 2016; (43): 1984-1988. [3]Kosuke Ebina, Motomu Hashimoto, Wataru Yamamoto, Toru Hirano, Ryota Hara, Masaki Katayama et al. Drug tolerability and reasons for discontinuation of seven biologics in elderly patients with rheumatoid arthritis. The ANSWER cohort study. PLoS ONE 14 (15):e0216624 Disclosure of Interests: None declared